Randomized feasibility trial of high-intensity interval training before elective abdominal aortic aneurysm repair. Issue 13 (9th October 2017) - Tew, G A; Batterham, A M; Colling, K; Gray, J; Kerr, K; Kothmann, E; Nawaz, S; Weston, M; Yates, D; Danjoux, G
Abstract: Background: This study assessed the feasibility of a preoperative high-intensity interval training (HIT) programme in patients awaiting elective abdominal aortic aneurysm repair. Methods: In this feasibility trial, participants were allocated by minimization to preoperative HIT or usual care. Patients in the HIT group were offered three exercise sessions per week for 4 weeks, and weekly maintenance sessions if surgery was delayed. Feasibility and acceptability outcomes were: rates of screening, eligibility, recruitment, retention, outcome completion, adverse events and adherence to exercise. Data on exercise enjoyment (Physical Activity Enjoyment Scale, PACES), cardiorespiratory fitness (anaerobic threshold and peak oxygen uptake), quality of life, postoperative morbidity and mortality, duration of hospital stay and healthcare utilization were also collected. Results: Twenty-seven patients were allocated to HIT and 26 to usual care (controls). Screening, eligibility, recruitment, retention and outcome completion rates were 100 per cent (556 of 556), 43·2 per cent (240 of 556), 22·1 per cent (53 of 240), 91 per cent (48 of 53) and 79–92 per cent respectively. The overall exercise session attendance rate was 75·8 per cent (276 of 364), and the mean(s.d.) PACES score after the programme was 98(19) ('enjoyable'); however, the intensity of exercise was generally lower than intended. The mean anaerobic threshold after exercise training (adjusted for baseline score and minimization variables) was 11·7 ml per kg per min in the exercise group and 11·4 ml per kg per min in controls (difference 0·3 (95 per cent c.i. –0·4 to 1·1) ml per kg per min). There were trivial-to-small differences in postoperative clinical and patient-reported outcomes between the exercise and control groups. Conclusion: Despite the intensity of exercise being generally lower than intended, the findings support the feasibility and acceptability of both preoperative HIT and the trial procedures. A definitive trial is warranted. Registration number: ISRCTN09433624 (https://www.isrctn.com/ ). Abstract : Precursor to a bigger trial